Effect of Sales Promotion, Website Quality, and Digital Marketing on Impulse Buying (Case Study on the Consumers of the Millennial Marketplace on Bukalapak in Semarang Region) - Rahma, Alina -; Haribowo, Putut -; Azizah, Azizah - (JOBS (Jurnal Of Business Studies), 2023)
This study aims to analyze the effect of Sales Promotion, Website Quality, and Digital Marketing on Impulse Buying (Case Study on Bukalapak's Millennial Generation Consumers in the Semarang Region). The data collection methods used were questionnaires, and literature studies. The questionnaire used is the Agree Disagree Scale with a score of 10 points (1-10) and the sample collection used is non-probability sampling, which does not provide equal opportunities/opportunities for each member or member of the population. Using a purposive sampling method, 100 samples of Bukalapak consumers were taken, who live in the Semarang area, and aged 25-40 years, and made purchases at Bukalapak more than once. The analysis technique used is validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, linearity test, multiple linear regression analysis, t test, F test and coefficient of determination using IBM SPSS 26. The results show that sales promotion, website quality, and digital marketing have a positive and significant effect on impulse buying. With a coefficient of determination of 45.1%